Echoes of the Life of Dora Pejačević’s Music on Croatian Radio - Tatjana Čunko (Arti Musices)
Radio Zagreb, today Croatian Radio (HR), began broadcasting on 15 May 1926, three years after the death of Dora Pejačević (Budapest, 10 September 1885 – Munich, 5 March 1923). Apart from two of the 24 opuses printed during her lifetime and one manuscript, her scores were not available in Croatia until 1972, when her legacy was deposited in the Croatian Music Institute. This article will first present an overview of the printed scores of the composer’s works available in Croatia, whose availability is one of the conditions for their public performances. Afterwards, HR documentary audio recordings of selected concerts and recordings made in HR studios will be presented. HR sends the best documentary and studio recordings for international exchange through the European Broadcasting Union (EBU), where they become available to all its members. Since HR rarely publishes its recordings as compact disc editions, but distributes them through the EBU network, and at the same time broadcasts Croatian and foreign discography editions, we will present them as well, and finally give an overview of the broadcasting of Pejačević’s works on HR’s channels from 2012 to 2023.